Increasing diversity in the nutrition, obesity, and diabetes biomedical workforce: the BRIDGES consortium - Newton, Jr, Robert L; Katzmarzyk, Peter T; Kenrik Duru, O; Lee, Anna; Irwin, Ashley; Mangione, Carol M; Morone, Natalia E; Ongeri, Elimelda Moige; Shaikh, Saame Raza; Stanford, Fatima Cody; Stanley, Takara L; Truesdale, Kimberly Parker (The American journal of clinical nutrition, 2025)
Scientists from diverse backgrounds are underrepresented (UR) in academia. This lack of diversity impedes scientific discovery and innovation. UR scientists tend to conduct research on issues relevant to UR populations, including chronic disease prevention and management, and health disparities. Difficulty in attaining grant funding is a major barrier preventing UR scientists from remaining in academia. Programs designed to provide UR scientists with career development training can help increase the number of UR scientists who obtain grant funding. These programs have shown some level of success, yet none have been specifically designed to target scientists conducting research pertaining to the interests of the National Institute for Diabetes, Digestive, and Kidney Disorders (NIDDK). Here, the Bringing Resources to Increase Diversity, Growth, Equity, and Scholarship for Obesity, Nutrition, and Diabetes Research (BRIDGES) consortium is described. BRIDGES is the first program to be funded by the NIDDK designed to increase the success rate of UR scientists competing for and obtaining funding related to nutrition, obesity, and diabetes. Four programs across the country, located in California, Massachusetts, North Carolina, and Louisiana, were funded in 2022. By design, some programmatic elements are shared across each of the funded programs, including mentoring and a pilot and feasibility funding program. Some elements are specific to each program. The BRIDGES program is expected to impact a substantial number of UR scientists who are then likely to have an influence on nutrition, obesity, diabetes, and health disparities research, shaping NIH priorities, and future scientists conducting NIDDK-related research.